2011
DOI: 10.1007/s10157-011-0452-y
|View full text |Cite
|
Sign up to set email alerts
|

Age, gender, and body length effects on reference serum creatinine levels determined by an enzymatic method in Japanese children: a multicenter study

Abstract: The reference serum Cr levels determined by an enzymatic method related to age, gender, and body length, and our linear and polynomial equations showing the relationship between body length and serum Cr level will be applicable for screening of renal function in Asian as well as Japanese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 9 publications
10
53
0
Order By: Relevance
“…Until recently, this value was still widely used in clinical work to assess kidney function. Our study showed that creatinine value increased gradually with age, a finding matched by those of Uemura et al (2011), who reported that serum creatinine concentrations in Japanese children differ significantly according to gender and age.…”
Section: Discussionsupporting
confidence: 72%
“…Until recently, this value was still widely used in clinical work to assess kidney function. Our study showed that creatinine value increased gradually with age, a finding matched by those of Uemura et al (2011), who reported that serum creatinine concentrations in Japanese children differ significantly according to gender and age.…”
Section: Discussionsupporting
confidence: 72%
“…The Japanese Society of Nephrology has issued precautions for use of eculizumab in patients with secondary TMA [21], which is classified according to underlying conditions or CACs [10,22]. Findings from a retrospective study suggest that the benefits of eculizumab vary in relation to the underlying condition of secondary aHUS [22].…”
Section: Discussionmentioning
confidence: 99%
“…MAHA was defined as a hemoglobin level of < 10 g/dL and thrombocytopenia as a platelet count (PLT) of < 15 × 10 4 /µL. AKI in children was defined as a serum creatinine level at least 1.5 times the upper limit of the age-and sex-specific pediatric reference range [10]. The approved eculizumab dosing is based on the patient's weight (Supplementary Table 1) [7].…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Regarding reference values, the PELOD (Performance of the Pediatric Logistic Organ Dysfunction)‐2 (Table 7(a))465 scoring system is widely used in international clinical research as an index of pediatric organ dysfunction, and do not necessarily match with the age‐specific reference values proposed in Japan (Table 7). 466 Because the serum creatinine value depends on the muscle mass, particularly in post‐pubescent patients, large gaps can arise between different genders and ethnicities, and may also result from differences in measuring methods (e.g., Jaffe method, enzyme method, etc. ), and validation will be necessary here as well.…”
Section: Cq19: Pediatric Considerationsmentioning
confidence: 99%